Hubungan Komorbid dan Adekuasi Hemodialisis dengan Survival Rate pada Pasien Hemodialisis di Rumah Sakit Islam Sultan Agung Semarang - Siti Naili Baroroh; Dwi Retno Sulistyaningsih; Indah Sri Wahyuningsih (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Hemodialysis is the primary therapy for patients with chronic kidney disease to maintain survival. The success of hemodialysis therapy is influenced by several factors, including comorbidities and hemodialysis adequacy. Comorbid conditions may increase the risk of complications, while hemodialysis adequacy plays an important role in determining therapeutic effectiveness and patient prognosis. This study aimed to determine the relationship between comorbidities and hemodialysis adequacy with survival rates among hemodialysis patients at Sultan Agung Islamic Hospital, Semarang. This quantitative study employed a cross-sectional design. A total of 175 hemodialysis patients were selected using purposive sampling. Survival analysis was performed using the Kaplan–Meier method to evaluate differences in survival rates based on comorbidities and hemodialysis adequacy. The results showed that most respondents had diabetes mellitus as a comorbidity (64.6%), adequate hemodialysis adequacy (58.9%), and were alive during the observation period (65.1%). Kaplan–Meier analysis demonstrated no significant difference in survival rates based on comorbidities, whereas a significant difference in survival rates was observed based on hemodialysis adequacy. Comorbidities were not associated with survival rate, while hemodialysis adequacy was significantly associated with survival rate among hemodialysis patients. Adequate hemodialysis is essential to improve patient survival.